RNA-sequencing Identifies Novel Pathways in Sarcoidosis Monocytes - Jaya Talreja (Nature Portfolio, 2017)
Abstract Sarcoidosis is a complex systemic granulomatous disorder of unknown etiology. Genome-wide association studies have not been able to explain a causative role for nucleotide variation in its pathogenesis. The goal of the present study was to identify the gene expression profile and the cellular pathways altered in sarcoidosis monocytes via RNA-sequencing. Peripheral blood monocytes play a role in sarcoidosis inflammation. Therefore, we determined and compared the transcriptional signature of monocytes from peripheral blood from sarcoidosis patients and healthy controls via RNA-sequencing. We found 2,446 differentially expressed (DE) genes between sarcoidosis and healthy control monocytes. Analysis of these DE genes showed enrichment for ribosome, phagocytosis, lysosome, proteasome, oxidative phosphorylation and metabolic pathways. RNA-sequencing identified upregulation of genes involved in phagocytosis and lysosomal pathway in sarcoidosis monocytes, whereas genes involved in proteasome degradation and ribosomal pathways were downregulated. Further studies are needed to investigate the role of specific genes involved in the identified pathways and their possible interaction leading to sarcoidosis pathology.